Structural Evidence for the Substrate Channeling of Rice Allene Oxide Cyclase in Biologically Analogous Nazarov Reaction - Yoeun, Sereyvath; Cho, Kyoungwon; Han, Oksoo (Frontiers in Chemistry, 2018)
Allene oxide cyclase (AOC) is a key enzyme in the jasmonic acid (JA) biosynthetic pathway in plants, during which it catalyzes stereospecific conversion of 12,13(S)-epoxy-9(Z),11,15(Z)-octadecatrienoic acid (12,13-EOT) to cis(+)-12-oxophytodienoic acid. Here, rice allene oxide cyclase (OsAOC) was localized to the chloroplast and its native oligomeric structure was analyzed by gel electrophoresis in the absence and presence of a protein-crosslinking reagent. The results suggest that OsAOC exists in solution as a mixture of monomers, dimers, and higher order multimers. OsAOC preferentially exists as dimer at room temperature, but it undergoes temperature-dependent partial denaturation in the presence of SDS. A heteromeric 2:1 complex of OsAOC and rice allene oxide synthase-1 (OsAOS1) was detected after cross-linking. The yield of cis(+)-12-oxophytodienoic acid reached maximal saturation at a 5:1 molar ratio of OsAOC to OsAOS1, when OsAOC and OsAOS1 reactions were coupled. These results suggest that the OsAOC dimer may facilitate its interaction with OsAOS1, and that the heteromeric 2:1 complex may promote efficient channeling of the unstable allene oxide intermediate during catalysis. In addition, conceptual similarities between the reaction catalyzed by AOC and Nazarov cyclization are discussed.